Cognitive Therapy of substance dependece - ibriam, samia; chaib, amira (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
The substance dependence phenomenon is considered an old and widespread in all societies of the world, a real threat to the individual, his health and social relations, and a threat to the state and its economy as well. This research aimed to identify the problem of substance dependence, its diagnostic criteria and how to treat it based on the principles and foundations of cognitive therapy, where the researchers addressed a set of elements that serve the topic in simple way.